2005
DOI: 10.1002/dvdy.20309
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial expression profile of the novelarmadillo-related gene,Alex2, during testicular differentiation in the mouse embryo

Abstract: In a screen for transcripts differentially expressed during gonadal development in mouse embryos, we identified the novel armadillo-related gene, Alex2. The armadillo (arm) family of proteins share a 42 amino acid tandem repeat motif called the arm domain, through which they interact with different binding partners. These intracellular proteins are implicated in a variety of developmental processes, including cell proliferation, migration, maintenance of tissue integrity, and tumorigenesis. Alex2 is a member o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…1C). This gene, ARMCX3, is a member of the ARMCX gene family about which little is known functionally (32)(33)(34). Direct interaction between Sox10 and ARMCX3 was confirmed by co-transfection of pACT2-ARMCX3 and pGBKT7-Sox10N100 in the yeast strain AH109 and subsequent growth on strict selection plates (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…1C). This gene, ARMCX3, is a member of the ARMCX gene family about which little is known functionally (32)(33)(34). Direct interaction between Sox10 and ARMCX3 was confirmed by co-transfection of pACT2-ARMCX3 and pGBKT7-Sox10N100 in the yeast strain AH109 and subsequent growth on strict selection plates (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…However, little is known about the function in drug resistance of the other genes found to commonly acquire methylation in tumours and cell lines at relapse and in drug-resistant SP populations. ARMCX2 might have a role in tumour suppression based on the presence of an armadillo repeat motif, which is found in other proteins fulfilling functions in cell proliferation, migration, maintenance of tissue integrity and tumourigenesis, and has been involved in development (Smith et al, 2005). MEST, a maternally imprinted gene, has been implicated in embryonic growth and maternal behaviour (Lefebvre et al, 1998), and loss of MEST imprinting has been reported in breast and lung cancers (Pedersen et al, 2002;Nakanishi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Arm protein lost in epithelial cancers, on chromosome X ( ALEX ; also known as armadillo repeat containing, X‐linked [ ARMCX ]) is a novel subgroup within the ARM family. The ALEX/ARMCX gene family consists of six genes including three predicted genes ( ALEX1‐6 ) . Bioinformatics analyses suggest that the ALEX1 , ALEX2 and ALEX3 are each encoded by a single exon and contain an N‐terminal transmembrane domain, some ARM repeat domains, and a DUF634 (domain of unknown function 634) .…”
mentioning
confidence: 99%
“…In addition, gene expression analysis revealed that both ALEX1 and ALEX2 mRNA is expressed in a variety of adult human tissues, including colon, but dramatically reduced or even undetectable in several human carcinoma cell lines and tissues . In mouse embryos, ALEX2 mRNA is expressed in the developing testis, forebrain and somites, and in dorsal root ganglia and ribs . In vivo RNAi screening for potential tumor suppressor genes using immortalized embryonic hepatocytes lacking p53 and overexpressing MYC revealed that knockdown of ALEX1 and ALEX2 individually accelerated hepatocarcinogenesis in mice .…”
mentioning
confidence: 99%